Portrait as a Method of Psychological Characterization in M. Saltykov-Shchedrin’s novel “The Golovlyov Family” and its Recreation in Armenian Translation - Atanesyan, Ashkhen (Bulletin of Yerevan University H: Russian Philology, 2024)
The article examines one of the particular problems that arise when translating M.Y. Saltykov-Shchedrin’s novel “The Golovlevs Family” into Armenian. We are talking about the full reproduction in translation of such an artistic detail as a portrait of a literary hero. “Portrait” in a literary work is a rather comprehensive concept that includes diverse characteristics of the hero. In this work, we limit ourselves to considering such a component of the portrait characteristics as the appearance of the heroes, which is not given much space in the work. It is known that in the creation of the main characters of a novel, the most significant is their speech characteristic. It is that characteristic that carries the main semantic and style-forming load. At the same time, the description of the appearance of the characters is also functional in the psychological characteristics of the image and plays an important role as a visual component of the reader’s perception. From this perspective, portraits of episodic, secondary and main characters of the novel are analyzed. It is shown how throughout the novel, in accordance with the development of the image, the physical appearance of the characters changes. Clothes are considered as an attribute of the hero’s appearance, which also has certain significance in revealing the image.The article provides a comparative analysis of the original and the Armenian translation of the novel within the boundaries of the identified issues. Examples of non-compliance of the translation with the original according to certain parameters are given and analyzed. Examples of adequate reproduction of the original in translation, which fully reflect the meaning and artistic originality of the original, are also considered. Based on the analysis, conclusions are drawn about how complete the artistic image is in the translation of the novel.
Keywords: image; portrait characteristics; character's appearance; psychologism; clothing; translation